Actively manipulating asymmetric photonic spin Hall effect with graphene. (30th September 2020) - Wu, Yaodong; Sheng, Lijuan; Xie, Linguo; Li, Sixian; Nie, Ping; Chen, Yu; Zhou, Xinxing; Ling, Xiaohui
Abstract: The photonic spin Hall effect (SHE), manifesting itself as spin-dependent splitting of light, holds potential applications in precise metrology and spin-based nanophotonic devices. Thus, it's highly desirable to control this effect at will. However, there lacks an active way for manipulating asymmetric spin splitting, i.e., the asymmetric splitting properties are fixed and cannot be dynamically modulated when the material is fabricated. In this work, we propose a simple and active method for manipulating the asymmetric in-plane spatial and angular shifts by considering a light beam reflected at the glass-air interface embedding with monolayer graphene. We theoretically establish the relationship between the in-plane spin shifts and the conductivity of graphene. We reveal that the in-plane spatial and angular shifts can be significantly adjusted and show obvious asymmetric features by changing the Fermi energy in graphene when the light beam is reflected near the Brewster and critical angles. Interesting, when the incident light is horizontally polarized, the optical shifts are more sensitive to the changes of Fermi energy near the Brewster angle than that near the critical angle. Finally, we propose a potential method that using spin angular shifts to directly detect the tiny variation of Fermi energy. Graphical abstract: Image 1